Toothbrushes may convey bacteria to the cystic fibrosis lower airways. Issue 1 (1st January 2019) - Passarelli Mantovani, Rebeca; Sandri, Angela; Boaretti, Marzia; Grilli, Alessandra; Volpi, Sonia; Melotti, Paola; Burlacchini, Gloria; Lleò, Maria M.; Signoretto, Caterina
ABSTRACT: Recent findings indicate that the oral cavity acts as a bacterial reservoir and might contribute to the transmission of bacteria to the lower airways. Control of a potentially pathogenic microbiota might contribute to prevent the establishment of chronic infection in cystic fibrosis. We evaluated the presence of CF microorganisms in saliva and toothbrushes of CF patients and verify their possible transmission to lower airways. Methods : We assessed the presence of P. aeruginosa, S. aureus, S. maltophilia, A. xylosoxidans, S. marcescens, and yeasts in saliva, toothbrushes and sputum of 38 CF patients and assessed the clonal identity of the strains occurring contemporary in multiple sites by PFGE. Results : At least one of the investigated species was isolated from 60 saliva samples and 23 toothbrushes. S. aureus was the most abundant species, followed by Candida spp. 31 patients contemporary had the same species in sputum and saliva/toothbrush: in most cases, clonal identity of the strains among the different sites was confirmed. Conclusion : Toothbrushes may be sources of oral contamination and might act as reservoirs favoring transmission of potentially pathogenic microorganisms from the environment to the oral cavity and eventually to the LAW. Oral hygiene and toothbrush care are important strategies to prevent CF lung infections.